Relationship between the Peripheral Lymphocyte Response to Mycophenolic Acid in vitro and the Level of ATP in Peripheral CD4+ Lymphocytes before and after Renal Transplantation - Sugiyama, K.; Tsukaguchi, M.; Sasahara, H.; Isogai, K.; Toyama, A.; Satoh, H.; Saito, K.; Nakagawa, Y.; Takahashi, K.; Tanaka, S.; Onda, K.; Hirano, T. (Drug Research, 2015)
Objective: The lymphocyte immunosuppressant sensitivity test has been used to predict the pharmacodynamics of immunosuppressive drugs for the purpose of preventing acute rejection and infection after renal transplantation. On the other hand, measuring the ATP levels in peripheral CD4+ lymphocytes is also able to monitor the risks of rejection and infection in transplant recipients. In the present study, we examined the relationship between the mycophenolic acid pharmacodynamics and the ATP levels in peripheral lymphocytes before and after renal transplantation.Methods: We examined both the pharmacological efficacy of mycophenolic acid and the lymphocyte ATP levels before and 2, 4 and 6 weeks after the operation in 20 renal transplant recipients. The drug’s pharmacological efficacy was evaluated by the 50% inhibitory concentration of the drug against the in vitro proliferation of peripheral blood lymphocytes activated by T cell mitogen. The ATP levels in peripheral CD4+ lymphocytes were measured by the Immuknow assay kit. The relationships between the mycophenolic acid pharmacodynamics and ATP levels in peripheral lymphocytes were examined in these recipients.Results: The immunosupressive effects of mycophenolic acid against mitogen-activated lymphocyte proliferation were significantly and positively correlated with the lymphocyte ATP levels, but only at 6 weeks after transplantation. The relationship was not significant before or at 2 or 4 weeks after the operation.Conclusion: Our present data raised the possibility that evaluating the pharmacological efficacy of mycophenolic acid pre-transplantation and monitoring the ATP level 6 weeks after transplantation can predict the risk of rejection and/or infection in renal transplant recipients.
Keywords: ATP quantitation assay; lymphocyte immunosuppressant sensitivity test (LIST); mycophenolic acid (MPA); peripheral blood mononuclear cell (PBMC); acute rejection; cytomegalovirus infection